KESANTUNAN TUTURAN YANG DIGUNAKAN PENGASUH DALAM PEMBENTUKAN KARAKTER ANAK JALANAN DI RUMAH SINGGAH - -, Ristiyani (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
This study is aimed to describe the function of politeness utterances used by nursemaid increating the character of street children in the Children Nations Shelter (RSAB)Soegijapranata Social Foundation (YSS) Semarang. This research is a qualitative descriptivestudy which designed with pragmatic approach triggered by Leech (1983) by basing its analysisfooting on the language functions (language functions) expressed concretely in speech acts. Theapproach is focused on the analysis of the utterances situation goal-oriented, linking a set ofprinciples conversation with their functions. The results of this study indicate nursemaidutterances who obey the principles of politeness of feeling maxim, kindness maxim, permissionmaxim, humility maxim, agreement maxim, and sympathy maxim have function as a tool increating the character of the street children who relate with themselves in relation to others,Adversity Quotient (Intellectual Quotient, Emotional Quotient, and spiritual quotient), theNation and state in relation to the world, and to the AlmightyGod